2007
DOI: 10.1152/ajprenal.00309.2006
|View full text |Cite
|
Sign up to set email alerts
|

Increased renal phosphodiesterase-5 activity mediates the blunted natriuretic response to ANP in the pregnant rat

Abstract: Knight S, Snellen H, Humphreys M, Baylis C. Increased renal phosphodiesterase-5 activity mediates the blunted natriuretic response to ANP in the pregnant rat. Am J Physiol Renal Physiol 292: F655-F659, 2007. First published September 26, 2006; doi:10.1152/ajprenal.00309.2006.-Normal rat pregnancy is characterized by plasma volume expansion due to renal sodium retention and is associated with a blunted response to natriuretic stimuli, such as atrial natriuretic peptide (ANP). ANP signals via cGMP, and phosphodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…This is consistent with our previous observations that the pregnant rat is refractory to the natriuretic actions of ANP (17) and exhibits a blunted acute pressure natriuresis (which is mediated by NO) (16,18). We also reported that intrarenal PDE5 inhibition will restore the natriuretic effect of ANP and NO in pregnant rats (14,29), further supporting a role for increased medullary PDE5 in the sodium retention of pregnancy. Overall, this selective blunting of the normal cGMP-dependent natriuretic influences, together with an underfill-activated renin, angiotensin, aldosterone system (30,32) will allow the sodium-retaining influences to predominate and cumulative PV expansion to occur.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with our previous observations that the pregnant rat is refractory to the natriuretic actions of ANP (17) and exhibits a blunted acute pressure natriuresis (which is mediated by NO) (16,18). We also reported that intrarenal PDE5 inhibition will restore the natriuretic effect of ANP and NO in pregnant rats (14,29), further supporting a role for increased medullary PDE5 in the sodium retention of pregnancy. Overall, this selective blunting of the normal cGMP-dependent natriuretic influences, together with an underfill-activated renin, angiotensin, aldosterone system (30,32) will allow the sodium-retaining influences to predominate and cumulative PV expansion to occur.…”
Section: Discussionsupporting
confidence: 92%
“…We hypothesize that an increase in renal PDE5 will degrade cGMP and inhibit the natriuretic response, contributing to the volume expansion of normal pregnancy. In support of this theory, we have demonstrated that selective, intrarenal PDE5 inhibition with sildenafil reverses the blunted response to infused ANP seen in normal pregnancy (14). Furthermore, this appears to be specific to cGMP-mediated natriuresis as cAMP-mediated (i.e., dopamine induced) natriuresis remains intact in pregnant rats (25).…”
mentioning
confidence: 52%
“…In inner medullary collecting duct cells isolated from pregnant rats, cGMP accumulation in response to ANP is reduced, and cGMP hydrolysis is increased compared with cells from virgin controls, and this is normalized by inhibition of PDE-5. Furthermore, PDE-5 inhibition in vivo reversed the blunted natriuresis to an infusion of ANP in pregnant rats (10).…”
Section: Discussionmentioning
confidence: 88%
“…In addition, selective, intrarenal PDE-5 inhibition with sildenafil reverses the blunted response to infused ANP seen in normal pregnancy (10). Increased renal PDE-5 will degrade cGMP and inhibit the normal natriuretic response, contributing to the volume expansion in normal pregnancy.…”
mentioning
confidence: 99%